2020
DOI: 10.3389/fmicb.2020.01291
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Major Bacteria and Yeast Species in Kefir Consortia by Multiplex TaqMan qPCR

Abstract: Kefir grains are complex microbial systems of several groups of microorganisms. The identification and quantification of the microbial composition of milk kefirs was described in several studies, which provided an insight into the microbial consortia in this complex ecosystem. Nevertheless, the current methods for identification and quantification are not appropriate for deeper studies on kefir consortia, e.g., population dynamics and microbial interactions in kefir grains. This requires another sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
1
18
1
Order By: Relevance
“…in various foods (Hong et al 2007 ; Tebbs et al 2011 ; Forghani et al 2016 ; Liu et al 2017 ; Heymans et al 2018 ; Parichehr et al 2019 ). In addition, several applications deal with probiotic or beneficial organisms, such as yeasts, Acetobacter spp., or different lactic acid bacteria (LAB) in kefir or starter cultures in cheese production (Bottari et al 2013 ; Nejati et al 2020 ). Moreover, the detection of food-spoiling bacteria, e.g., Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…in various foods (Hong et al 2007 ; Tebbs et al 2011 ; Forghani et al 2016 ; Liu et al 2017 ; Heymans et al 2018 ; Parichehr et al 2019 ). In addition, several applications deal with probiotic or beneficial organisms, such as yeasts, Acetobacter spp., or different lactic acid bacteria (LAB) in kefir or starter cultures in cheese production (Bottari et al 2013 ; Nejati et al 2020 ). Moreover, the detection of food-spoiling bacteria, e.g., Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their growth can be stimulated or altered. A mutualism relationship was identified between a nitrogen formation yeast strain and a Lactococcus lactis, another important observation being related to the lactose that contributes to an easiest interaction between L. lactis and Saccharomyces cerevisiae [84]. Stadie et al contrasted the growth of the co-cultivation vs. a pure culture of key representative water kefir isolates.…”
Section: Kombuchamentioning
confidence: 99%
“…Wang et al [28] reported the use of fluorescence in situ hybridization (FISH) and real-time quantitative PCR (RT-qPCR), demonstrating that L. kefiranofaciens was the only dominant bacterial species in Tibetan kefir grains (Table 1). Recently, multiplexed qPCR assays, using dual-labeled oligoprobes of TaqMan assay, which anneal specifically to a target region, were developed in order to specifically detect and quantify several microorganisms in kefir grains and beverages' microbial communities and consequently evaluate their population dynamics and microbial interactions [38]. Primer-probe sets targeting species-specific genes were designed for six bacteria and five yeasts, among them L. kefiranofaciens (Table 1).…”
Section: Culture-independent Approachesmentioning
confidence: 99%
“…Grains, China CD Ropy colonies [21] Grains, China CI - [45] Grains and beverages, Brazil CI - [47] Grains and beverages, Ireland CI - [31] Grains and beverages, Turkey CD, CI Not detected [29] Grains, Turkey CI - [55] Grains, Brazil CI - [46] Grains, Slovenia CD, CI 40 [48] Grains, Argentina CD, CI 11 [27] Grains, Turkey CI - [51] Grains, China CD, CI 11 [44] Grains, Italy CD, CI - [23] Grains, Korea CI - [37] Grains, Belgium CI - [50] Grains, Brazil CD, CI 5 [22] Grains, USA CI - [56] Grains, Russia CD, CI Not detected [30] Grains and beverages, Ireland, France, United Kingdom CI - [34] Grains, Malaysia CI - [57] Grains, Turkey CI - [35] Grains, China CD, CI 18 [28] Kefir and beverages, China CI - [58] Beverages, Korea CI - [59] Grains, China CI - [60] Grains, Turkey CD 3 [61] Grains, Greece CI - [62] Beverage, Korea CI - [63] Grains and beverages, Germany, Italy CI - [38] Grains and beverages, United Kingdom, Caucuses region, Ireland, Lithuania, South Korea, USA CI - [64] Grains, China, Germany, USA CI - [65] Grains, China CD, CI 1 [66] CD: culture-dependent method; CI: culture-independent method; -: isolation not performed.…”
Section: Origin Detection Number Of Isolates Referencementioning
confidence: 99%
See 1 more Smart Citation